There are two ways to do this
Method 1:
Find (fg)(x) first
(fg)(x) = f(x)*g(x)
(fg)(x) = (x^2-19)*(20-x)
(fg)(x) = 20x^2-x^3-380+19x
(fg)(x) = -x^3+20x^2+19x-380
Then plug in x = -10
(fg)(x) = -x^3+20x^2+19x-380
(fg)(-10) = -(-10)^3+20(-10)^2+19(-10)-380
(fg)(-10) = -(-1000)+20(100)+19(-10)-380
(fg)(-10) = 1000+2000-190-380
(fg)(-10) = 3000-570
(fg)(-10) = 2430
-----------------------------------------
Method 2:
Find f(-10)
f(x) = x^2 - 19
f(-10) = (-10)^2 - 19
f(-10) = 100 - 19
f(-10) = 81
Find g(-10)
g(x) = 20-x
g(-10) = 20-(-10)
g(-10) = 20+10
g(-10) = 30
Multiply the two results
(fg)(-10) = f(-10)*g(-10)
(fg)(-10) = 81*30
(fg)(-10) = 2430
-----------------------------------------
Whichever method you pick, the answer is: 2430